Features of a simple partnership agreement in the aspect of law enforcement practice - N. A. Temnikova (Правоприменение)
Introduction. The contract of a simple partnership, on the one hand, has been well known since Roman law, on the other hand, we see that clearly insufficient legal regulation creates gaps. The understanding of the features of the contract in research papers is very differ. The development of legislation providing for the possibility of creating investment partnerships, partnerships for the purpose of participating in regular transportation of passengers and baggage, in the provision of paid services at train stations and bus stations shows the expediency of studying this type of contract. The above creates the need for a deeper study of the features of the contract in order to identify the features of its application in civil turnover.Goal. The purpose of the study is to identify the features of a simple partnership agreement that affect its legal qualification and law enforcement. Methodology. In the course of the research, methods of generalization, description, analysis, synthesis, comparative, historical and formal legal methods were used.Results. A simple partnership agreement is a multilateral transaction, the participants of which are not divided into active and passive parties. Their wills are co-directed to achieve a certain economic result. The contract of a simple partnership is organizational, since its content consists of the rights and obligations for interaction, information, and the procedure for carrying out the activities of the partners, which can be designated as an internal legal relationship of the participants. The contract historically refers to fiduciary, but for investment partnerships, and, de lege ferenda, for business partnerships, the degree of fiduciary is weakening.